Autophagy in the pathogenesis of ankylosing spondylitis. Issue 6 (June 2016) - Ciccia, Francesco; Haroon, Nigil
Abstract The pathogenesis of ankylosing spondylitis (AS) is not well understood, and treatment options have met with limited success. Autophagy is a highly conserved mechanism of controlled digestion of damaged organelles within a cell. It helps in the maintenance of cellular homeostasis. The process of autophagy requires the formation of an isolation membrane. They form double-membraned vesicles called "autophagosomes" that engulf a portion of the cytoplasm. Beyond the role in maintenance of cellular homeostasis, autophagy has been demonstrated as one of the most remarkable tools employed by the host cellular defense against bacteria invasion. Autophagy also affects the immune system and thus is implicated in several rheumatic disease processes. In this article, we explore the potential role of autophagy in the pathogenesis of AS.